The impact of ESG ratings under market soft regulation on corporate green innovation: an empirical study from informal environmental governance - Chen, Cheng; Fan, Min; Fan, Yaojun (Frontiers in Environmental Science, 2023)
Enhancing corporate green innovation is a crucial pathway towards achieving a green economic transformation. Diverging from the literature focusing on government environmental regulations and hard regulatory approaches, this study investigates how market soft regulation intervenes in corporate green innovation. From the perspective of informal environmental governance, this paper employs a multi-period difference-in-differences empirical model to examine the impact of ESG ratings on corporate green innovation. The findings reveal that ESG ratings have a positive influence on corporate green innovation. Specifically, ESG ratings encourage firms to increase the number of green patents application and authorization, thereby stimulating investment and innovation activities in the realm of green innovation. These conclusions remain robust after undergoing various statistical tests. In the analysis of moderating effects, this paper discovers a negative inhibitory effect of financing constraints on the relationship between ESG ratings and corporate green innovation. Additionally, the study finds that ESG ratings exhibit a more pronounced promotion effect on green innovation among high-pollution and high-quality information disclosure firms. The research emphasizes the importance for enterprises to undertake proactive strategic adjustments and provides insights for optimizing existing green development policies.